含自旋禁止系统的二酰亚胺光致发光材料及其制法与应用 (2025)
本发明公开了一种含自旋禁止系统的二酰亚胺光致发光材料及其制法与应用。所述二酰亚胺光致发光材料具有如下式中任一者所示的结构：#imgabs0#本发明提供的含自旋禁止系统的二酰亚胺光致发光材料具有可实现荧光、延迟荧光以及室温磷光三发射的特点，磷光寿命最高可达数百毫秒，延迟荧光达到数百微秒，在有机光致发光领域有着很大的应用前景。 The invention discloses a diimide photoluminescent material containing a spin prohibition system as well as a preparation method and application of the diimide photoluminescent material. The diimide photoluminescent material has a structure shown in any one of the following formulas: the diimide photoluminescent material containing the spin prohibition system provided by the invention has the characteristics of realizing three-emission of fluorescence, delayed fluorescence and room-temperature phosphorescence, the phosphorescence lifetime can be up to hundreds of milliseconds, the delayed fluorescence can be up to hundreds of microseconds, and the phosphorescence emission can be up to hundreds of microseconds. The compound has a great application prospect in the field of organic photoluminescence.